Panorama atual dos Richardiidae (Insecta: Diptera) na Amazônia: avanços e desafios para os taxonomistas - Brandão, Elifas de Oliveira (Brasil, 2025)
The Richardiidae family, part of the Tephritoidea superfamily, represents a relatively small group of flies, encompassing 193 valid species distributed within 32 genera and divided into two subfamilies: Richardiinae and Epiplateinae. The current distribution of Richardiidae is restricted to the New World, with the most species recorded in the Neotropical Region. Richardiids can be recognized by their slender to robust body, head lacking frontal setae, one orbital seta, a reduced prosternum that is either bare or setose, a well-developed katepisternum with a height greater than that of the anepisternum, and wing with a Costal vein with a break and a pre-apically swollen R1 vein. This monograph aims to conduct a bibliographic review of the current state of knowledge on Richardiidae to clarify the status of this family in the Amazon region. Data from scientific articles, monographs, dissertations, and theses related to the taxonomy, systematics, and biology of Richardiidae were analyzed. Additionally, representatives of the family deposited in the Zoological Collection Prof. Paulo Bührnheim (UFAM) and the Invertebrate Collection of the National Institute for Amazonian Research (INPA), both located in Manaus, Amazonas, Brazil, were studied. These Richardiidae specimens were identified to the generic level using the key by Wendt and Ale-Rocha (2012). The external morphology of the specimens was studied under a stereoscopic microscope. Photographs were taken using a Leica M165 C stereomicroscope equipped with a Leica MC 170 HD camera, and the images were edited and assembled using Adobe Photoshop. Diagnoses were prepared for each identified genus, highlighting the differential morphological characteristics. The geographic records of the studied specimens were plotted on maps using QGIS version 3.36, based on coordinate data obtained from the labels of each specimen. Based on the literature, 24 genera with geographic distributions in the Amazon Region were recognized. A total of 83 publications related to these genera were identified.